2014
DOI: 10.1021/jo4022666
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of 3-Azido- and 3-Aminopiperidines by Intramolecular Cyclization of Unsaturated Amines

Abstract: A highly efficient one-pot synthesis of 3-azidopiperidines has been achieved by an intramolecular cyclization of unsaturated amines that allows for the nucleophilic installation of an azide moiety. This method unlocks the versatile employment of the azide functionality in the preparation and biological studies of piperidine-containing structures. This strategy has been expanded for the direct incorporation of a variety of nitrogen nucleophiles, and thus it provides a rapid and modular synthesis of 3-amino and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 91 publications
0
21
0
Order By: Relevance
“…A number of representatives of this class exhibit glycosidase inhibitory activity or antimetastatic, anticancer, antitumour or anti-HIV properties [13]. A large number of natural products contain an indolizidine framework, among them (−)-δ-coniceine, (−)-swainsonine, indolizidine 167B [410], (+)-lentiginosine [1115], (+)-slaframine [16], (−)-elaeokanine C [17], (+)-cyclizidine [18], lepadiformine [19], the highly oxygenated (+)-castanospermine [2021], or pumiliotoxin [22]. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A number of representatives of this class exhibit glycosidase inhibitory activity or antimetastatic, anticancer, antitumour or anti-HIV properties [13]. A large number of natural products contain an indolizidine framework, among them (−)-δ-coniceine, (−)-swainsonine, indolizidine 167B [410], (+)-lentiginosine [1115], (+)-slaframine [16], (−)-elaeokanine C [17], (+)-cyclizidine [18], lepadiformine [19], the highly oxygenated (+)-castanospermine [2021], or pumiliotoxin [22]. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, when N -chloroamine 11a , which is bench stable and can be isolated as a white solid, was treated with KI, we did not observe the formation of 11b via the ESI-MS study, but 126 or 127 was observed upon the treatment with KI, 12 , and Cs 2 CO 3 . This result suggests that the formation of 126 or 127 from a combination of 11 /NIS or 11 /NCS/KI might occur via different reaction mechanisms and chloroamine 11a did not undergo a simple chloride-iodide exchange process to form iodoamine 11b while such chloride-iodide exchange process is commonly proposed in literature 42 , 48 .
Fig.
…”
Section: Discussionmentioning
confidence: 70%
“…Very recently, Berhal and Prestat reported the aminocyclization/azidation of alkenyl oxy-ureas, oxy-carbamates, and oxy-amides with an [Fe­(OAc) 2 /phenanthroline] catalytic system and TMSN 3 , giving azido-containing five-membered heterocyclic rings (Scheme , eq 3) . The NCS-promoted one-pot conversion of a series of unsaturated amines into the corresponding 3-azidopiperidines has been performed by Kang and co-workers in the presence of NaI and NaN 3 . Studer and a co-worker and Li and co-workers performed the intermolecular aminoazidations of olefins by copper and iron catalysis, respectively, using TMSN 3 in the presence of N -fluorobenzenesulfonimide .…”
mentioning
confidence: 99%